2023
DOI: 10.1002/pssr.202300224
|View full text |Cite
|
Sign up to set email alerts
|

Al Incorporation up to 99% in Metalorganic Chemical Vapor Deposition‐Grown Monoclinic (AlxGa1–x)2O3 Films Using Trimethylgallium

Abstract: Growths of monoclinic (AlxGa1−x)2O3 thin films up to 99% Al contents are demonstrated via metalorganic chemical vapor deposition (MOCVD) using trimethylgallium (TMGa) as the Ga precursor. The utilization of TMGa, rather than triethylgallium, enables a significant improvement of the growth rates (>2.5 μm h−1) of β‐(AlxGa1−x)2O3 thin films on (010), (100), and (01) β‐Ga2O3 substrates. By systematically tuning the precursor molar flow rates, growth of coherently strained phase pure β‐(AlxGa1−x)2O3 films is dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…The process of alloying is a prevalent technique utilized to modify the properties of materials, and it is extensively employed within the semiconductor industry. The growth of alloying on the material itself presents numerous advantages over the combination of different materials. This is exemplified in the AlGaN/GaN HEMT, where the lattice mismatch is relatively small, and the interface quality is adequate for practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…The process of alloying is a prevalent technique utilized to modify the properties of materials, and it is extensively employed within the semiconductor industry. The growth of alloying on the material itself presents numerous advantages over the combination of different materials. This is exemplified in the AlGaN/GaN HEMT, where the lattice mismatch is relatively small, and the interface quality is adequate for practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…An orbital hybrid appears with the formation of β-AlGaO to change the position of E C , 14 achieving the goal of widening the bandgap and making it more suitable for extreme environmental power electronics applications. At present, the epitaxial growth of β-AlGaO on Ga 2 O 3 has been widely studied, 15–17 Zhang reported ∼2790 cm 2 V −1 s −1 low-temperature mobility in the β-AlGaO/Ga 2 O 3 heterostructure. 18 Okumura et al demonstrated β-AlGaO metal–semiconductor field effect transistors.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its promising fundamental material properties, such as a large energy bandgap (4.8 eV), , controllable n-type doping, and a high predicted breakdown field strength (8 MV/cm), β-Ga 2 O 3 has emerged as a promising semiconductor candidate for the development of next-generation high-power electronic devices . Another key advantage of β-Ga 2 O 3 over other wide (GaN, SiC) and ultrawide (diamond, AlN) bandgap semiconductors is the availability of high-quality, single-crystalline native substrates with various orientations, enabling high-quality epitaxy of β-Ga 2 O 3 , and β-(Al x Ga 1– x ) 2 O 3 alloys. While the technology is in its nascent stage, significant strides have been made in creating β-Ga 2 O 3 -based devices using bulk and epitaxial thin films, such as lateral and vertical field-effect transistors and Schottky barrier diodes (SBDs) with high breakdown voltages surpassing 6 kV. …”
Section: Introductionmentioning
confidence: 99%